Application of BP Neural Network Model in Risk Evaluation of Railway Construction. (2nd June 2019) - Changwei, Yang; Zonghao, Li; Xueyan, Guo; Wenying, Yu; Jing, Jin; Liang, Zhu
Abstract : Chinese railway construction project is an important part of the implementation of the "Belt and Road" strategy, and the risk evaluation of overseas railway construction is the primary link of the project. Firstly, this paper mainly analyzes the Asian and European countries along the railway construction project, establishes a railway construction project risk evaluation system, and synthesizes various risk factors. Secondly, it establishes two independent BP neural network models by using different training algorithms because of the different political, economic, and cultural elements between the two continents.